2015
DOI: 10.7342/ismt.rpics.2015.1.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Calcular e apresentar tamanhos do efeito em trabalhos científicos (1): As limitações do p < 0,05 na análise de diferenças de médias de dois grupos

Abstract: A Revista Portuguesa de Investigação Comportamental e Social exige que os autores sigam as recomendações do Publication Manual of the American Psychological Association (APA, 2010) na apresentação da informação estatística. Uma das recomendações da APA é de que os tamanhos do efeito sejam apresentados associados aos níveis de significância estatística.Uma vez que os valores de p decorrentes dos resultados dos testes estatísticos não informam sobre a magnitude ou importância de uma diferença, devem entã… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0
23

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(61 citation statements)
references
References 66 publications
0
38
0
23
Order By: Relevance
“…A possible reason for the data is not significant is that the LBPG presented low intensity of pain, with VAS of 0.89 ± 1.67cm on the day of the test. When we observed the electromyographic percentage values we noticed greater muscle activation in the LBPG when compared to the CG, for this reason, the effect size analysis was done, although the p value gives the probability of obtaining a significant statistic, it does not report on the clinical or practical importance of the results (26) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A possible reason for the data is not significant is that the LBPG presented low intensity of pain, with VAS of 0.89 ± 1.67cm on the day of the test. When we observed the electromyographic percentage values we noticed greater muscle activation in the LBPG when compared to the CG, for this reason, the effect size analysis was done, although the p value gives the probability of obtaining a significant statistic, it does not report on the clinical or practical importance of the results (26) .…”
Section: Discussionmentioning
confidence: 99%
“…M1 represents the mean of the LBPG, M2 is the CG average and the DP is the combined standard deviation (2.25) . The classification used was: low effect 0.20, medium 0.50 and value equal to or higher than 0.80 as a high effect, analyzed using the G * Power software (2,25,26) . (1) Table 1 presents the results of the characteristics of LBPG and CG participants.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, GEE was used to test the main effects of NW in asymmetrical variables, and the Bonferroni post hoc test was performed to identify the significant differences at α < 0.05. Also, the effect size (ES) was calculated using the Hedges' g considering trivial (<0.20), small (0.20-0.49), moderate (0.50-0.79), large (>0.80), and too large (>1.30) effects between pre and post-tests at more affected and less affected segments in the asymmetrical variables [30,31]. Statistical analysis was performed by a highly trained researcher who was blinded to the participants, using SPSS software (Statistical Package for Social Sciences, version 21.0).…”
Section: Discussionmentioning
confidence: 99%
“…The results presented here indicated that all used risk measures were valid in terms of the contrasting groups, confirming results from previous research studies. Regardless of the effects, the intensity was low; Nevertheless, it might still be relevant (Espirito-Santo & Daniel, 2015) due to the difficulty in standardizing risk-taking measures (Boyer, 2006) and a greater human inclination to risk aversion (Linde & Vis, 2016;Weber et al, 2004).…”
Section: Discussionmentioning
confidence: 99%